Dual Coding Method to Stimulate Memory in Early Childhood - Susanti, Dwi; Kristiana, Dian; Rusdiani, Nurtina Irsad (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to describe the implementation of the Dual Coding Method to stimulate the memory of early childhood students at TK Aisyiyah Ngebel. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings reveal that the Dual Coding Method for stimulating memory in young children at TK Aisyiyah Ngebel consists of three main stages: planning, execution, and evaluation. During the planning stage, teachers design learning materials that integrate both text and images. In the execution stage, teachers engage in active interaction with the children to discuss and visualize concepts, enhancing their understanding and retention. The evaluation stage focuses on assessing the children's memory stimulation. The results indicate that the Dual Coding Method is effective in stimulating memory in early childhood students. Children's memory abilities are shown to be strong, as evidenced by their attentiveness, ability to retain material presented by the teacher, and recall of the provided information. This method has successfully facilitated better memory retention among the young learners. The study concludes that the Dual Coding Method is a beneficial approach for enhancing memory in early childhood education, supporting children in paying close attention, retaining, and recalling the information learned.